2014
DOI: 10.1021/jp410918c
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Nanosheets and Layered Hybrids of MoS2 and WS2 through Exfoliation of Ammoniated MS2 (M = Mo,W)

Abstract: Ammoniated MS 2 (M = Mo,W) have been synthesized by reacting Li x MS 2 with a saturated solution of ammonium chloride. While, largely neutral NH 3 is present in the interlayer of ammoniated MoS 2 , equal amounts of NH 3 and NH 4 + ions are present in the tungsten analog. The ammoniated MS 2 exfoliate readily in a variety of polar solvents with exfoliation being best in water. Ammoniated WS 2 forms a more stable colloidal dispersion compared to the Mo analog because the ammonium ions do not deintercalate easily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
180
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(196 citation statements)
references
References 58 publications
(125 reference statements)
14
180
2
Order By: Relevance
“…However, the ammoniated MoS 2 presents a single endothermic peak centered at 80 °C corresponding to NH 3 . [65] The intercalated species contains both [66,67] The reaction is as follows:…”
Section: Ammonia Intercalationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the ammoniated MoS 2 presents a single endothermic peak centered at 80 °C corresponding to NH 3 . [65] The intercalated species contains both [66,67] The reaction is as follows:…”
Section: Ammonia Intercalationmentioning
confidence: 99%
“…[70] Co-stacking of exfoliated MoS 2 and WS 2 monolayer dispersions results in formation of MoS 2 −WS 2 hybrid with an interlayer spacing of 0.65 nm. [65] Conducting polyethylene oxide (PEO) intercalated MoS 2 (PEOMoS 2 ) with expanded interlayer spacing by the exfoliation/restacking route has been investigated. [71][72][73][74] In a typical process (Figure 4A) Figure 4B).…”
Section: Ammonia Intercalationmentioning
confidence: 99%
See 1 more Smart Citation
“…Dispersion of bulk MoS 2 in solvents, particularly in water, and its exfoliation into few layers nanosheet is a critical step towards exploring its application [2,4,5,7]. Since the surface of MoS 2 is hydrophobic, it is challenging to exfoliate and disperse it in water without using surfactants or surface modification.…”
Section: Synthesis and Characterization Of Paa-mos 2 Nanosheetsmentioning
confidence: 99%
“…The bulk MoS 2 consists of S Mo S sheets stacked by weak van der Waals interactions, which provide their unique mechanical, chemical and physical properties [5]. It has been shown that the MoS 2 obtained from the delamination of layers through mechanical cleavage or liquid exfoliation, exhibited outstanding performance in various applications as compared with bulk MoS 2 [2,[6][7][8]. Therefore, deposition of a few layers of MoS 2 is highly desirable and could be particularly useful for various applications including hydrodesulfurization [9] and hydrogen evolution catalysis [3].…”
Section: Introductionmentioning
confidence: 99%